2014
DOI: 10.18632/oncotarget.2034
|View full text |Cite
|
Sign up to set email alerts
|

20(S)-Ginsenoside Rg3 is a novel inhibitor of autophagy and sensitizes hepatocellular carcinoma to doxorubicin

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related deaths worldwide. High mortality from HCC is mainly due to widespread prevalence and the lack of effective treatment, since systemic chemotherapy is ineffective, while the targeted agent Sorafenib extends median survival only briefly. The steroidal saponin 20(S)-ginsenoside Rg3 from Panax ginseng C.A. Meyer is proposed to chemosensitize to various therapeutic drugs through an unknown mechanism. Since autophagy often serves as cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 68 publications
4
83
0
Order By: Relevance
“…Here we demonstrate that doxorubicin induces protective autophagy in pancreatic cancer cells. Consistently, another report has described doxorubicin induced autophagy during induction of cell death [8]. Furthermore, pharmacologic or genetic inhibition of autophagy by knockdown of Beclin-1 or Atg5 expression augments doxorubicin-induced cell death in multiple myeloma cell lines [28].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Here we demonstrate that doxorubicin induces protective autophagy in pancreatic cancer cells. Consistently, another report has described doxorubicin induced autophagy during induction of cell death [8]. Furthermore, pharmacologic or genetic inhibition of autophagy by knockdown of Beclin-1 or Atg5 expression augments doxorubicin-induced cell death in multiple myeloma cell lines [28].…”
Section: Discussionmentioning
confidence: 56%
“…In cancer, autophagy plays important roles both in cell death and survival [7,8]. Autophagy is activated in response to a number of stressors, including cancer chemotherapeutics, facilitating cell survival and leading to treatment resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the increased acidification and cathepsin enzyme activity, which are the unique features of autophagosome–lysosome fusion, have also been found to be concomitantly altered . Ro and 20( S )‐Rg3 were identified as novel autophagy inhibitors that blocked the fusion of autophagosome with lysosome. More detailed mechanistic studies revealed that Ro led to ROS generation via ESR2 (estrogen receptor 2) mediated NCF1/p47PHOX (neutrophil cytosolic factor 1) pathway, which resulted in an impairment in both lysosomal acidification and cathepsin activity …”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
“…Doxorubicin‐induced autophagy plays a protective role in hepatocellular carcinoma (HCC) cells. In addition, 20( S )‐Rg3 treatment synergized with doxorubicin to inhibit tumor growth of HCCs . Ro as a novel autophagy suppressor, enhanced 5‐fluorouracil (5‐Fu)‐induced DNA damage and sensitized chemoresistant esophageal cancer cells to 5‐Fu‐mediated cell death .…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
“…22,23 Many molecular mechanisms have been proposed for such anticancer activity, Downloaded by [University of Cambridge] at 17:58 16 June 2016 6 including autophagy regulation. [24][25][26][27] Moreover, autophagy contributes to the neuronal protective effects of ginsenoside Rb1 and compound K. 28,29 However, there is currently no evidence showing a direct connection between autophagy and ginsenoside-induced cell death.…”
Section: Introductionmentioning
confidence: 99%